Minority language ownership and authority: perspectives of native speakers and new speakers. Issue 1 (2nd January 2018) - Nic Fhlannchadha, Siobhán; Hickey, Tina M.
ABSTRACT: The Irish language is a minority language undergoing the attenuation and accelerated change commonly seen as threatened languages come under increasing pressure from the dominant language. The decline of the numbers of traditional speakers and growing numbers of L2 speakers of Irish has given rise to some contested spaces regarding authenticity, accuracy and ownership of the language, as well as who has the right to produce and distribute the resources associated with/generated by the language. This study explored the attitudes and experiences of native and high-proficiency L2 speakers ('new speakers') of Irish with respect to these issues. Semi-structured interviews were conducted with 17 Irish speakers, 7 young adult native speakers (four female, aged 18–26 years) and 10 young adult high-proficiency new speakers (six female, aged 19–31). Thematic Analysis showed a significant decline, in the view of both groups, in the confidence and authority of native speakers of Irish, and a change to a view among both groups that goodwill and commitment to the language's maintenance is more important than linguistic accuracy. The commonalities and differences between the native speaker and new speaker groups are explored, and the implications for the future of Irish are considered.